(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
There is no doubt that the relationship between commercial openness and economic growth is still the subject of great controversy. The research aims to analyze the long-term causal relationship between agricultural trade openness and agricultural growth by using Toda-Yamamoto methodology to verify the existence of a causal relationship between them in Iraq during the period (2003-2021) via using annual time series data, aiming at the importance of opening horizons, for new studies. The results showed that there is no causal relationship in any direction between agricultural trade openness and agricultural growth in Iraq during the period studied. Despite Iraq’s openness to global trade and the increased flow of exported and imported agricultural products, the agricultural sector did not show a noticeable improvement in productivity or growth or diversity in crops is a result of this openness. The study indicates that structural factors, such as weak agricultural infrastructure, lack of investment in technology, and the absence of sufficient government support, are the factors most affecting agricultural growth in Iraq. Accordingly, the study recommends that the focus be on improving these factors may be more effective in achieving sustainable agricultural growth rather than relying solely on trade openness policies. These results emphasize the importance of adopting a comprehensive and integrated approach to improving the agricultural sector in Iraq, which takes into account the structural, technical, and financing aspects, to achieve the goals of sustainable agricultural development.